FENOMENA WANITA KARIR KETIKA PERCERAIAN - Muhammad Zainuddin Sunarto (Fakultas Agama Islam Universitas Nurul Jadid, 2021)
'Iddah is a waiting period that must be lived by a woman due to the termination of the marital relationship, either due to divorce or death, in order to restore mental or physical condition after being left by her husband. The implementation of 'iddah in the jahiliyyah period is considered no longer appropriate to be applied today because, at that time, a wife whose husband died would be placed in a hut (a small, fragile, and old house), given the ugliest clothes, not allowed to wear clothes. Perfume, so that the smell is very unpleasant, then brought himar animals, goats, or birds and then occupied with him. The majority of women today have a myriad of activities outside the home as career women, which sometimes makes some of them the backbone of the family, whether they are with their husbands or not. Some scholars' to leave the house, if it is in an emergency, the state of emergency is understood differently by ulama' Usul al-fiqh. Such as, al-Shatibi understands the meaning of emergency with an essential need to be maintained. a woman whose husband dies, then she has to provide for her family, then she is allowed to leave the house because she is in an emergency